Hambatan Pekerja Sosial Masyarakat dalam menjalankan peran dan fungsi kepada penyandang disabilitas - Jandrea Putri, Yunda; Dewi, Susi Fitria; Fatmariza, Fatmariza; Irwan, Irwan (Departemen Ilmu Sosial Politik Universitas Negeri Padang, 2025)
This research aims to describe the role of Community Social Workers for people with disabilities in IV Jurai District, and to identify obstacles to Community Social Workers in carrying out their roles and functions for people with disabilities in IV Jurai District. The method used in this research is qualitative. The informants in this study were 7 people determined through purposive sampling. Data collection techniques are carried out through observation, interviews and documentation. Test the validity of the data using source triangulation. The research results show that the role of Community Social Workers for people with disabilities is to a) take the initiative to help with administrative management of people with disabilities, b) provide social assistance information and emotional support to people with disabilities, c) help people with disabilities to obtain their rights them, such as rights to education, health and employment, d) assist the nagari government in providing complete data related to disabilities. Furthermore, the Social Community obstacles in carrying out their roles and functions for people with disabilities are a) Lack of PSM training and skills, b) Limited internet network for data processing. and c) Lack of professionalism among PSM members.